The Study of The Usage of Vacuum Preloading Method in The Construction Project Of Palembang – Indralaya Toll Road - Laili Ervianty; Hary Christady Hardiyatmo; Suryo Hapsoro (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
Palembang – Indralaya (Palindra) Toll Road is part of the Trans Sumatera Toll Road built on soft soil. Soil improvement using vacuum preloading method has been conducted to resolve the problem. The method involves replacing a surcharge load with an atmospheric pressure and utilizing vertical and horizontal drains, as well as sand blanket. Factors that influence the effectivity of the performance of the vacuum method comprise the settlement, the time of settlement, the speed of settlement, the degree of consolidation, the distance of the Prefabricated Vertical Drain or PVD, and so forth. The result of the settlement using Terzaghi’s equation combined with Indraratna’s showed that the addition of the height of the fill would have been effective if it had been equal or larger than the vacuum pressure that was used (80 kPa). It could be observed from attaining faster consolidation time of 56 days. The analysis result was, then compared with the final settlement by using Asaoka method. The design of the PVD distance by using vacuum method showed that the spacing (S) was less restrained, which was 1,23 m, compared to the one using with extra load (surcharge) which was 1,2 m. The settlement of vacuum consolidation was 1,98 m, which was smaller than the surcharge one that reached 2,11 m.